African swine fever in Uganda : description of a recent outbreak and possible differential diagnoses - Andersson, M. (Swedish University of Agricultural Sciences, 2011)
This study had two different aims. The main aim was to investigate the dynamics and impact of African swine fever (ASF) on a farm in Uganda during a recent outbreak through a case study. The second aim was to estimate the presence of two important differential diagnoses of ASF: Classical swine fever (CSF) and Porcine Reproduction and Respiratory syndrome (PRRS). The field and laboratory based case study of the farm level dynamics of ASF virus during a recent outbreak (October-December 2010) on a farm in the district of Mityana, Uganda, was conducted, using interviews, ELISA and RT-PCR. The financial impact on the farm was also estimated. The impact of the outbreak was profound. The farmer lost approximately over half of the population of pigs; mainly adults and newborn piglets were affected. Weaners and older piglets survived to a relatively larger extent. The outbreak spread between pens and units probably via direct and indirect contact. The source of the infection was difficult to identify since there were several suspected sources.A pilot study of presence CSF and PRRS in Uganda was conducted using ELISA and RT-PCR in a cross-sectional study on 239 samples from the district of Rakai in southern Uganda and 80 samples from reported outbreaks of mortality in pigs where ASF virus had not been confirmed as the cause. All samples were negative for CSF and only one sample was seropositive for PRRS. The one positive sample for PRRS was suspected to be a false positive.